Unwrapping techniques for speckle phase maps: study and comparison of the performance of principal methods - Lopes, H. (2012)
Holographic interferometry (HI) techniques are powerful tools for experimental mechanics which can be used to assess displacement fields on a loaded object surface. Used with no contact and high resolution HI can be combined with image methods for data analysis. Nevertheless, the speckle should be fully resolved by the image detector to digitally record an interferogram. This leads to a noisy recording which difficult it’s post-processing. Each measurement with HI ends normally in a phase map computation representing the object displacement. Phase calculation algorithms are based on spatial or temporal phase modulation and lead to wrapped phase maps. To obtain the continuous phase distribution several solutions have been implemented. This paper describes the main filtering and unwrapping algorithms available and compares it´s performance to solve discontinuities in noisy phase maps.